Предмет: Алгебра,
автор: misssashapetr
Помогите пожалуйста
Упростить выражение
(а-1)(а+1)-а(а+4) при а=12
Ответы
Автор ответа:
0
а²-1-а²-4а=-4а-1
При а=1/2
-4*1/2-1=-2-1=-3
Ответ:-3
При а=1/2
-4*1/2-1=-2-1=-3
Ответ:-3
Автор ответа:
0
В ответе
Автор ответа:
0
а то значит целое?
Автор ответа:
0
Ну да
Автор ответа:
0
что это значит?
Автор ответа:
0
Ладно проехали. Спасибо
Автор ответа:
0
А^2-1-а^2-4а=-1-4а=-1-2=-3
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Биология,
автор: nigarayakupova
Предмет: Английский язык,
автор: sabinadilbekova
Предмет: Русский язык,
автор: dashenkacute
Предмет: Алгебра,
автор: geor27
Предмет: Физика,
автор: ingaorlova79